Development of Primary Education in Ukraine in the Second Half of the XX - Beginning of the XXI Centuries: Historic Base of the Research - Havrylenko, Tetyana (Pedagogical Discourse, 2013)
In the article the author systematizes and analyzes the historic base of the research of the problem of the primary education development in Ukraine in the second half of the 20th –beginning of the 21st centuries from the point of view of the modern methodology. Depending on the origin, the content and the scientific value such groups of sources have been defined and characterized, as legislative and normative documents; materials of pedagogical congresses, theoretical and practical conferences, pedagogical readings, enlightening meetings; statistical materials; educational and methodological literature; materials of periodicals. It has been ascertained that these sources are widespread and stored in the archives. It has been pointed up that during the source basis research of the problem defined little known and unknown documents, materials, papers etc have been found, which will be introduced into the scientific circulation. The further research prospects are seen in a thorough analysis of such sources group as pedagogues scientific papers relevant to the investigated period.